Intestinal Atresia: Twenty Years of Experience at a Reference Hospital - Sarac, Mehmet; Tartar, Tugay; Bakal, Unal; Aydin, Mustafa; Akdeniz, Ibrahim; Kazez, Ahmet (Istanbul Training & Research Hospital, 2021)
Introduction: The aim of this study was to reveal the factors that affect the clinical outcomes of patients undergoing surgery in our university hospital for intestinal atresia (IA) and to share our experience. Methods: We analyzed data from 74 newborns with IA who underwent surgical treatment between January 1997 and December 2016. Results: The study population consisted of 40 female and 34 male newborns with a mean age at diagnosis of 6.4 +/- 8.3 days. The mean birth weight was 2.3 +/- 0.6 kg, the mean gestational age was 35.6 +/- 2.8 weeks, the mean maternal age was 28.9 +/- 6.1 years, and the mean hospitalization time was 24.5 +/- 25.3 days. Duodenal atresia was the most common diagnosis (n=31, 42%) and colonic atresia the least common (n=2, 3%). The longest and shortest mean hospital stays occurred in patients with jejunal (32.8 +/- 41.6 days) and those with colonic (8 +/- 0 days) atresia, respectively. Although the survival rates were low in newborns with either intestinal or duodenal atresia (80% or 81%, respectively), all patients with pyloric or colonic atresia survived. Of the patients who died, 82% (9/11) had additional congenital abnormalities (X-2=8.461, p=0.004), which included major cardiac defects (n=3), Down syndrome (n=2), biliary atresia (n=1), esophageal atresia + tracheoesophageal fistula + anal atresia + tracheal atresia (n=1), esophageal atresia + tracheoesophageal fistula (n=1), and microcephaly (n=1). The mean hospital stay of patients with or without additional abnormalities was 26.4 +/- 21.4 or 23.04 +/- 28.04 days, respectively (p=0.207). Conclusion: Among newborns with IA, duodenal atresia was the most common diagnosis and colonic atresia the least common. Additional congenital abnormalities negatively affect the hospital stay and mortality rate of newborns with IA.
Keywords: Intestinal atresia; surgical treatment; hospital stay; mortality; newborn